INDONESIA'S FOREIGN POLICY IN CREATING SECURITY STABILITY IN INDO-PACIFIC REGION - Mariane Olivia Delanova; Yanyan Mochamad Yani (Journal Of Global Strategic Studies, 2021)
Indonesia as one of the countries that is included in the Indo-Pacific Region has an important role in creating security stability in the Region. As the center point of the Indo-Pacific, Indonesia certainly thinks about the right defense strategy to be able to play an active role in the region. Undoubtedly, this action will be related to Indonesia's free-and-active foreign policy. As a region that has strategic points, countries in the Indo-Pacific Region carry out an agenda to be able to solve problems in a peaceful way by increasing mutual trust. Naturally, it will make the Indo-Pacific Region as a central region in the future. Based on the findings, Indonesia's foreign policy takes part in an active role at the international level by promoting the concept of cooperation in the Indo-Pacific Region to increase mutual trust between countries. In addition, countries in the region participate in mutually beneficial openness in order to create security stability in the region. Indonesia's foreign policy is considered to be appropriate and useful in the midst of situations in competing for having influence in the region. Thus, Indonesia's role in the Indo-Pacific cannot be separated from the character of Indonesia's current foreign policy which emphasizes “middle power” and leadership in the region.